Plankton community dynamics based on vertical gradients and transparency in Lake Rawa Pening - Trismara, Belia Kharisma Balqis; Rahman, Arif; Jati, Oktavianto Eko (Acta Aquatica: Aquatic Sciences Journal, 2025)
The eutrophic conditions of Rawa Pening waters results in the rapid growth of water hyacinth (Eichhornia crassipes). The uncontrolled presence of water hyacinth affects the intensity of sunlight entering the water column and affects plankton abundance. The purpose of this study was to determine the vertical distribution of plankton abundance, the main factors affecting plankton abundance, and plankton associated with light intensity. The study was conducted in January and July 2024 using survey methods, with a total of 3 stations and 2 depths (0 m and 1 m). The statistical analysis used was the t-test and simple linear regression, Pearson correlation test, and multivariate analysis using Nonmetric Multidimensional Scaling (NMDS) with envfit analysis. The results showed that depth did not significantly affect the abundance of phytoplankton and zooplankton, but sampling time in January and July had an effect on the abundance of phytoplankton. The types of phytoplankton found were Chloropyceae, Bacillariophyceae, Cyanophyceae, Zygnematophyceae, Trebouxiophyceae, Euglenophyceae, and Chrysophyceae, while the zooplankton found were Monogononta, Branchiopoda, and Maxillopoda. Phytoplankton abundance values ranged from 740,447 - 3,650,523 cells/L, while zooplankton abundance ranged from 0 - 3,335 ind/L. There was no significant (homogeneous) relationship between light intensity and phytoplankton abundance based on the results of NMDS and envfit association analysis. Nitrate levels significantly affected plankton abundance based on the r value (0.901) and R2 (0.812). Keywords: Abundance, Envfit, Plankton, Rawa Pening, Vertical Distribution